Setting the cultural agenda for domestic readers: A corpus analysis of news translation in Culture Weekly - Ping, Yuan (Frontiers in Communication, 2022)
Drawing on the notion of cultural translation and agenda-setting theory, this study examines the role that translation plays in facilitating cross-linguistic and cross-cultural communication within the context of news translation. It is based on a case study of Culture Weekly – a four-page section published every Monday in Reference News, the most widely circulated daily newspaper in China. This study analyzes a comparable corpus of Chinese news articles from Culture Weekly and their English-language versions from various media outlets between February and March 2022. The study finds that the newspaper mainly used strategies of acculturation and literal translation and that it set the agenda for its domestic readers by highlighting particular cultural issues and disseminating certain cultural values. This case study provides insight into how news translation, as a form of recontextualization, strikes a delicate balance between accuracy and acceptability and how it mediates between source and target cultures within the institutional setting. The resulting translation reflects the editorial attitudes of the media outlet towards various cultural issues and manifests the relationship between the newspaper and its readership.